UNESCO building factors Thailand’s Kalasin learning city and citizenship - Kathanyoo Kaewhanam; Phimlikid Kaewhanam; Ariya Pongsiri; Jariya Intanin; Sirinada Kamolkat; Eko Priyo Purnomo; Atthapong Sirisuwun (International Journal of Evaluation and Research in Education (IJERE), 2023)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) promotes the city of learning and lifelong learning. The UNESCO factors influencing the construction of Kalasin Learning City in Thailand. This framework is applied in the study on Kalasin learning city. This research analyzes the relationship between citizenship and learning city from 500 Kalasin citizens, who responded to a questionnaire based on citizenship factors affecting the UNESCO city of learning. Where statistical analysis of average standard deviation and Multiple regression analysis of 10 others asked to participate in the interview found that it promoted learning from primary to higher education. Strong support for a lifelong learning culture. It has a statistically significant positive impact on citizenship (group level) at .05, so the factors that need to promote promotion to improve citizenship (group level) are the promotion of learning from primary to higher education. The interview results also supported data from the questionnaire. The results suggest that building Kalasin learning city requires a common factor. That states the implications of the findings and identifies possible new research fields as developing online participation processes under the COVID-19 pandemic to align with the online learning model, which is also a modern learning model.